2007
DOI: 10.2337/dc06-2009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Disease Characteristics on the Efficacy of Duloxetine in Diabetic Peripheral Neuropathic Pain

Abstract: OBJECTIVE -To evaluate the impact of baseline disease variables related to diabetes and diabetic neuropathy severity on efficacy and safety of duloxetine in the management of diabetic peripheral neuropathic pain.RESEARCH DESIGN AND METHODS -The impact of baseline conditions was evaluated using the data from three pooled placebo-controlled studies for combined duloxetine, doses of 60 mg q.d. and 60 mg b.i.d., versus placebo. The primary efficacy measure was the weekly mean of 24-h average pain severity, and nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 21 publications
2
36
0
4
Order By: Relevance
“…Registration studies of pregabalin (Lyrica, Pfizer, New York, NY), duloxetine (Cymbalta, Eli Lilly, Indianapolis, IN), and gabapentin (Neurontin, Pfizer) had a placebo change in pain severity by PI-NRS or PI-VAS (cm) from À 0.3 to À 1.7 at 8 to 12 weeks for PDN or postherpetic neuralgia [(last observation carried forward (LOCF)]. [2][3][4][5][6][7][8][9][10][11][12] Fourteen to 22 week clinical trials of lamotrigine (Lamictal, GlaxoSmithKline, London, UK), topiramate (Topamax, Johnson and Johnson, New Brunswick, NJ), and oxcarbazepine (Trileptal, Novartis, Basel, Switzerland) that failed to demonstrate a consistent treatment effect in PDN and neuropathic pain had a placebo change in PI-NRS from À 1.5 to À 2.2 (LOCF). [13][14][15][16][17][18] Large and variable improvement of pain scores in the placebo group may make it more difficult to detect true medication effects.…”
mentioning
confidence: 99%
“…Registration studies of pregabalin (Lyrica, Pfizer, New York, NY), duloxetine (Cymbalta, Eli Lilly, Indianapolis, IN), and gabapentin (Neurontin, Pfizer) had a placebo change in pain severity by PI-NRS or PI-VAS (cm) from À 0.3 to À 1.7 at 8 to 12 weeks for PDN or postherpetic neuralgia [(last observation carried forward (LOCF)]. [2][3][4][5][6][7][8][9][10][11][12] Fourteen to 22 week clinical trials of lamotrigine (Lamictal, GlaxoSmithKline, London, UK), topiramate (Topamax, Johnson and Johnson, New Brunswick, NJ), and oxcarbazepine (Trileptal, Novartis, Basel, Switzerland) that failed to demonstrate a consistent treatment effect in PDN and neuropathic pain had a placebo change in PI-NRS from À 1.5 to À 2.2 (LOCF). [13][14][15][16][17][18] Large and variable improvement of pain scores in the placebo group may make it more difficult to detect true medication effects.…”
mentioning
confidence: 99%
“…This result is consistent with an analysis of 3 clinical trials of painful DPN that suggested that medication vs placebo differences were greater in subjects with greater baseline pain intensity. 31 Considered together, these data suggest that neuropathic pain RCTs should use a pain inclusion criterion of at least 40 on a 0 to 100 scale (alternatively 4 on a 0-10 scale) to decrease the likelihood that studies of efficacious treatments will have falsely negative outcomes. We also found that age was associated with assay sensitivity, with greater subject age being associated with larger effect sizes.…”
mentioning
confidence: 99%
“…In several large trials, P Ͻ 0.10 has been interpreted as a significant test for treatment effect modification in subgroup analysis (interaction), despite increasing the chance of type I error, 21,22 yet cautious interpretation of the interaction terms is required for the NASCET results. The seeming benefit may be in part due to chance variation in the rates of stroke at 2 yr among surgically treated patients with CKD compared with those with preserved renal function (5.6 versus 9.5% respectively; Table 2).…”
Section: Discussionmentioning
confidence: 99%